Emergence of advanced immunotherapy: New horizons for HPV-negative head and neck squamous cell carcinoma - Madhan Krishnan; Shyamaladevi Babu; M.V. Vinaya Kumar; Rajasekaran Subbarayan (Oral Oncology Reports)
Head and neck squamous cell carcinoma (HNSCC) is a complex group of malignancies that exhibit distinct clinical and molecular characteristics, especially in the HPV-negative subset. The treatment landscape for HPV-negative HNSCC has historically been limited to surgery, radiation, and chemotherapy, with these modalities often yielding suboptimal outcomes. The emergence of advanced immunotherapy represents a paradigm shift, offering new therapeutic options for this challenging cancer type. This review provides a comprehensive analysis of the latest advancements in immunotherapy for HPV-negative HNSCC, focusing on, chimeric antigen receptor (CAR) T-cell therapy, therapeutic cancer vaccines and immune checkpoint inhibitors. It also explores the potential benefits and limitations of combining immunotherapy with other treatment modalities including chemotherapy, targeted therapy, and radiation. Key challenges, including tumor heterogeneity, immunosuppressive microenvironment, and resistance mechanisms, are discussed. The review concludes with a look at future research directions and strategies to overcome these challenges and improve patient outcomes.